2022
DOI: 10.3390/bioengineering9060253
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Clinical Environment Security Analysis Using Reinforcement Learning

Abstract: Many communication standards have been proposed recently and more are being developed as a vision for dynamically composable and interoperable medical equipment. However, few have security systems that are sufficiently extensive or flexible to meet current and future safety requirements. This paper aims to analyze the cybersecurity of the Integrated Clinical Environment (ICE) through the investigation of its attack graph and the application of artificial intelligence techniques that can efficiently demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Another traditional reinforcement approach was employed in our prior work [ 5 ] to determine the best route an attacker may follow to compromise an integrated clinical environment system, and the algorithm utilized was based on Q-learning. Both Q-learning and SARSA rely on tables to store value.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another traditional reinforcement approach was employed in our prior work [ 5 ] to determine the best route an attacker may follow to compromise an integrated clinical environment system, and the algorithm utilized was based on Q-learning. Both Q-learning and SARSA rely on tables to store value.…”
Section: Resultsmentioning
confidence: 99%
“…Both Q-learning and SARSA rely on tables to store value. In [ 5 ], one target node was the lone node in the attack graph, which had seven nodes. It was found that the Q-learning results showed the shortest path, independent of the cumulative reward, as opposed to the SARSA algorithm, which disregarded the shortest path, such as 1 → 3 → 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, the technology at our disposal offers cost-effective solutions to these problems. Machine learning (ML) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], artificial intelligence (AI) [16][17][18][19][20][21][22][23][24][25][26][27][28][29] and Big Data [30][31][32][33][34][35] can provide robust and innovative answers to long-standing problems.…”
Section: Introductionmentioning
confidence: 99%